Identification and functional analysis of histone 1.2-like in red sea bream (Pagrus major). (January 2023) - Song, Lianfei; Soomro, Maqsood Ahmed; Wang, Lingshu; Song, Yuting; Hu, Guobin
Abstract: Histone H1 acts as an essential chromatin component and participates in the formation of higher chromatin structures together with core histones. In addition, H1 also has important functions in physiological processes such as gene expression regulation, DNA repair, and the immune response. In this study, the histone homologous protein Pm-H1.2-like was identified from the transcriptome database of Pagrus major we studied previously. Conservatism of evolution was investigated by sequence alignment and phylogenetic analysis. Transcripts of Pm-H1.2-like were detected in P. major tissues. The highest expression level was found in gill and skin tissues. Consistent with the data from the transcriptome database, we observed that the expression of Pm-H1.2-like was rapidly induced in nonspecific cytotoxic cells (NCCs) infected with inactivated Vibrio anguillarum . Gene silencing of Pm-H1.2-like by RNAi significantly suppressed the expression of NK-lysin and GZMB in NCCs at 12 h after pathogen stimulation, but had no significant effect on IFN-γ expression. Next, we obtained the fusion proteins rPm-H1.2-like and rPm-H1.2-like (36–80) through prokaryotic expression. ELISA showed that rPm-H1.2-like bound to oligonucleotide (ODN) in a concentration-dependent manner, while no binding activity of rPm-H1.2-like (36–80) with ODN was observed. This study confirmed that Pm-H1.2-like actively participates in the immune response of NCCs to bacterial infection, deepening the understanding of the immune features of histone H1 in fish. Highlights: Histone H1 homologous protein Pm-H1.2-like was identified in Pagrus major. RNAi of Pm-H1.2-like suppressed the expression of NK-lysin and GZMB but not IFN-γ. rPm-H1.2-like but not rPm-H1.2-like (36–80) could bind to OND.